Hubungan Kumpulan Mineral Berat pada Sedimen Pantai dan Lepas Pantai dengan Batuan Asal Darat di Perairan Teluk Pelabuhan Ratu, Jawa Barat - Deny Setiady (Indonesian Journal on Geoscience, 2010)
DOI: 10.17014/ijog.v5i1.93Based on the depth contour, the sea bottom morphology in southern part of the researched area is very steep, while in the northern area it is sloped slightly. It shows that sedimentation process is from south to the north and continues to the west. It is supported by the current process in studied area. Rock slope stability of hilly morphology in the Cimandiri River area is related to weathering, erosion, and transportation process in coastal and nearshore areas. The presence of mineral in the studied area caused by those processes, was accumulated in the mouth of Cimandiri River, coastal, and nearshore areas. Those minerals were deposited in Cibelendung to Karangbeureum nearshore area by the longshore current. Magnetite and pyroxene minerals are dominant along the coastal and offshore areas of Pelabuhan Ratu Bay. The presence of augite and diopside shows that the source rock is basic igneous rocks (basalt), while the presence of hornblende and biotite minerals tend to indicate that the source rock is intermediate igneous rocks (andesite).